KEEPING HIGHER EDUCATION RELEVANT VIA THE MEDIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 19 May 2015 – The media plays an important role in ensuring the success of the National Higher Education Development Plan and the continued relevance of higher education in Malaysia which goes beyond simply preparing graduates for entry into the media industry, to encompass the creation of a synergy between media and higher education that results in an educated populace befitting the status of a developed nation.